Sustainability powered by digitalization? (Re-)politicizing the debate - Florian Steig; Pascal D. Koenig; Jens Marquardt; Angela Oels; Jörg Radtke; Rainer Rehak; Sabine Weiland (Sustainability: Science, Practice, & Policy)
As ecological crises escalate, various stakeholders frame digitalization as a key solution for sustainability transformations. Besides incremental optimization, this promise has not materialized yet. We argue that digital solutions toward sustainability objectives are shaped by and reinforce power structures that effectively undermine sustainability outcomes. Academic discourse and governance are often dominated by a technology-centric framing in contrast to technologically informed, power-centric approaches. In this article, we develop an interdisciplinary framework to analyze three interconnected dimensions of power at the sustainability-digitalization-nexus and reveal how they obstruct sustainability. We locate power at the levels of environmental knowledge, governance, and technological materiality. First, digital technologies create representations of the environment that reinforce, reconfigure, or clash with preexisting ones, striving for more and better digital real-time data for technological control. Second, the spread of digital technologies is facilitated by emerging actor coalitions that promote digitalization while employing a reductionist understanding of sustainability. This narrows the policy space to optimization and incremental solutionism, which reproduces the status quo. Finally, the designs and material infrastructures of current digital technologies create path dependencies and lock-in effects while the underlying colonial resource and wealth flows remain hidden. We advocate for a (re-)politicization of digitalization across these dimensions to leverage its potential for sustainability transformations. We conclude that digitalization cannot spare us from political conflicts and deliberation processes about desirable sustainability futures. The debate should re-center fundamental questions about what kind of sustainable futures we want, where technology has a role to play, and where it does not.